Level of Knowledge in Medical Students about Gender-related Differences in Ischemic Heart Disease - Cabrera, Erika Vanesa; Levin, Ricardo (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Background: Ischemic heart disease is the leading cause of mortality worldwide in female patients and presents gender-related differences in clinical presentation. Women usually have their first presentation of coronary disease 10 years later than men and with a marked increase in mortality. Anatomically, they have smaller diameter coronary arteries, have worse results when exposed to cardiovascular risk factors, and have gender-specific risk factors. Little is known about the perception that medical students have in this regard. Material and methods: Descriptive, cross-sectional, observational study; in which medical students were surveyed. Results: A survey was carried out on 70 students, both sexes, between the ages of 23 and 47, who were in the 5th and 6th year, in which it was found that the majority perceived breast cancer as the leading cause of female mortality and no to cardiovascular disease; recognition of classic cardiovascular risk factors continued and few observed the existence of gender-specific cardiovascular factors; the recognition of typical symptoms of acute coronary syndrome persisted and the presence of symptoms that predominate in women was ignored. Conclusion: Most of the students did not recognize ischemic heart disease as the main cause of death in women globally, awareness strategies should be proposed about the differences that women present in cardiovascular disease